The value of embedding work-integrated learning and other transitionary supports into the first year curriculum: Perspectives of first year subject coordinators - Milliken, Hannah; Dean, Bonnie; Eady, Michelle J. (Journal of teaching and learning for graduate employability, 2021)
The first year of university, also known as the first year experience (FYE), is a crucial time for students as they learn a range of new practices that enable them to study and pursue a discipline or profession of interest. The function of this transitionary time however in relation to providing both a successful transition into university as well as an orientation to the profession is under-developed. Work-integrated learning is a leading pedagogy in tertiary institutions to build student's career-readiness by applying theory within work experiences. However, despite the growth of WIL across discipline contexts, little is known about the prevalence and impact of WIL practices within the first year of tertiary study. The purpose of this study was to explore the perspectives of those who design and facilitate first year subjects on the value of embedding WIL and other transitionary supports into the first year curriculum. A qualitative case study was employed, with interviews from ten first-year subject coordinators within a single degree and institution. The findings reveal three crucial areas of transition in the first year: 'Transition into learning, Transition into being a student, and Transition into becoming a professional'. Recommendations centre on benefits of a whole-ofcourse approach to transition and WIL for developing students with the necessary knowledge and skills to succeed both at university and into the workplace.